Improvement in reactiveness of realtime trajectory smoothing - Ling, Weng Hong (Nanyang Technological University, 2022)
Human-robot collaboration has been an advancing topic throughout the years. Therefore for human-robot collaboration to work safely and efficiently, a real-time system must be fully developed. One important part of the system is the Realtime Motion Planning (RMP). RMP requires extremely fast computation throughout the whole process from detecting obstacles to planning of trajectories. However, by just being able to do RMP is not enough as with RMP only the path executed will be jerky.